Rb and Tumorigenesis - Fanciulli, Maurizio (Medical Intelligence Unit, 2006)
Rb and Tumorigenesis examines how recent advances have demonstrated the interaction of Rb with chromatin remodeling enzymes. This new title explores the potential roles of these interactions in Rb functions and provides some evidence that distinct Rb co-repressor may target different genes in different phases of the cell cycle.